Scientific and pedagogical schools of therapy and preventive medicine - S. Yu. Astanina; R. N. Shepel; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
On October 5, 2023, on the initiative of the National Medical Research Center for Therapy and Preventive Medicine and with the support of the Russian Society for the Prevention of Noncommunicable Diseases, the III International Research and Practice Forum "Scientific and Pedagogical Schools of Therapy and Preventive Medicine" was held. The Forum included two areas: symposiums dedicated to the best practices of higher education institutions; round tables dedicated to problems of education and practice integration. Scientific and pedagogical schools of the Far Eastern State Medical University, Siberian State Medical University, Samara State Medical University, Northern State Medical University, Smolensk State Medical University, S. I. Georgievsky Medical Institute of the V. I. Vernadsky Crimean Federal University were represented. Scientists and practicing doctors representing the following educational organizations took part in the discussion of integration of medical education and practical healthcare: Belgorod National Research University, Kemerovo State Medical University, Medical Institute of the Derzhavin Tambov State University, V. F. Voino-Yasenetsky Krasnoyarsk State Medical University, Academy of Postgraduate Education of the Federal Scientific and Clinical Center, Research Medical Center "Gerontology", Multifunctional Medical Center (Tashkent, Republic of Uzbekistan), Ulaanbaatar Songo Hospital (Ulaanbaatar, Mongolia), First Pavlov State Medical University of St. Petersburg, Yaroslavl State Medical University, Volgograd State Medical University, Volgograd Regional Clinical Hospital № 3, National Medical Research Center for Therapy and Preventive Medicine of the Russian Ministry of Health. The Forum showed that many medical higher educational institutions of the country have formed both independent scientific and pedagogical schools of fundamental biomedical sciences, therapy, preventive medicine, which have national and international recognition, and those that are intensively developing in accordance with Russian and international principles and demands of practical healthcare. The presence in medical education of authoritative scientific and pedagogical schools of therapy and preventive medicine is one of the indicators of the effectiveness of universities and academies in training internists and general practitioners.